Selective adsorption and separation of dyes from an aqueous solution on organic–inorganic hybrid cyclomatrix polyphosphazene submicro-spheres1. Issue 8 (28th February 2015) - Wei, Wei; Lu, Rongjie; Xie, Haojie; Zhang, Yifan; Bai, Xue; Gu, Li; Da, Rui; Liu, Xiaoya
<x xml:space="preserve">Abstract</x> Poly(cyclotriphosphazene-co-4, 4′-sulfonyldiphenol) (PZS) submicro-spheres were easily prepared, which exhibited a selective adsorption and separation of dyes that can be classified as Lewis acids and/or Brønsted acids by acid–base interactions.